The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10681-010-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for functional analysis of effectors from cereal rust fungi

Abstract: With the advancement of several Puccinia genome sequencing projects, along with gene expression data and methods for predicting secreted proteins, it is now possible to predict many effector proteins from the cereal rusts. Biological assays that can be conducted in a relatively high throughput fashion are necessary to assign specific functions, such as avirulence. Biolistic delivery of potential effectors is limited by the need to examine individual cells and delivery by Agrobacterium generally also affects sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 43 publications
2
49
0
1
Order By: Relevance
“…Recently, a bacterial type III secretion system (T3SS) assay for delivery of fungal effectors into wheat, using the expression/delivery vector pEDV6 and Pseudomonas fluorescens effector‐to‐host analyzer (EtHAn) strain, has been established (Yin and Hulbert, ; Upadhyaya et al ., ). Hence, we overexpressed PSTha5a23 in wheat cv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a bacterial type III secretion system (T3SS) assay for delivery of fungal effectors into wheat, using the expression/delivery vector pEDV6 and Pseudomonas fluorescens effector‐to‐host analyzer (EtHAn) strain, has been established (Yin and Hulbert, ; Upadhyaya et al ., ). Hence, we overexpressed PSTha5a23 in wheat cv.…”
Section: Resultsmentioning
confidence: 99%
“…Avocet Susceptible (AvS) using this assay to further investigate the role of PSTha5a23 in plant immunity modulation. eGFP and bacterial effector AvrRpt2 that can trigger HR in wheat (Innes et al ., ; Yin and Hulbert, ) were used as a negative and positive control respectively. EtHAn is non‐pathogenic on wheat (Yin and Hulbert, ) and inoculation of EtHAn in wheat could not trigger a detectable necrotic or chlorotic reaction phenotype on wheat plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This crucial phase is still in its infancy [38,39] and will most likely be limited to testing a handful of candidate genes in the initial stages. Several groups have attempted to modify existing heterologous expression systems from other pathosystems to establish a reliable method for testing rust AVR effector candidates in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have attempted to modify existing heterologous expression systems from other pathosystems to establish a reliable method for testing rust AVR effector candidates in wheat. This includes delivery of effector candidates directly into wheat cells by expressing them in bacterial pathogens for delivery by the type III secretion system [39] or through virus-mediated approaches [40]. Alternatively, host-induced gene silencing could be utilized to transiently silence and test PST pathogenicity or virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…syringae 61 hrp/hrc cluster (T3SS machinery) stably integrated into the chromosome, thereby making this nonpathogenic bacterium T3SS competent for effector delivery. This was shown to function for delivery of various P. syringae effectors into A. thaliana (Thomas et al 2009), andYin andHulbert (2010) found that P. fluorescens EtHAn expressing AvrRpm1 or AvrRpt2 induced H 2 O 2 production in wheat, suggesting that it may be suitable for effector delivery in cereals. In this study, we report the development of an efficient system of effector delivery into wheat, based on T3SS delivery by P. fluorescens EtHAn, which has enabled the screening of candidate Puccinia graminis f. sp.…”
mentioning
confidence: 99%